Capacidad funcional y desempeño de pacientes con neumonía por Covid-19 - Bravo C, Eusebio; Rivera-Lillo, Gonzalo; Gallegos B, Sebastián; Horta M, Paula; Navarro A, Rocío; Puppo G, Homero; Torres-Castro, Rodrigo (Revista Hospital Clínico Universidad de Chile, 2021)
One year after the first case reported by a new coronavirus (COVID-19), the evidence hasshown a series of persistent signs and symptoms once the acute process has been overcome.Under the WHO’s framework for health and disability, these impairments at cardiorespiratory,cognitive, and musculoskeletal body functions and structures lead, at least in the short andmid-term, to activity limitations and participation restriction. In this review, we discussed themain alterations generating disability and the challenges of implementing effective evaluationstrategies in this disease. Along with their role in the health emergency, rehabilitation teamsare challenged to design and deliver timely intervention strategies to reduce post-COVID-19disability.